Recurrent Chordoma Resection in the Advanced Multimodality Image Guided Operating Suite: 2-Dimensional Operative Video. Issue 5 (15th April 2021) - Ibn Essayed, Walid; Almefty, Kaith K; Al-Mefty, Ossama
Abstract: Recurrent skull base chordomas are challenging lesions. They already had maximum radiation, and in the absence of any effective medical treatment, surgical resection is the only treatment. 1, 2 Surgery on recurrent previously radiated chordomas, however, carries much higher risk and the likelihood of subtotal resection. Maximizing tumor resection allows longer tumor control. 3-5 The Advanced Multimodality Image Guided Operating Suite developed at the Brigham and Women's Hospital, Harvard Medical School, with the support of the National Institutes of Health, provides an optimal environment to manage these tumors. It offers the capability to obtain and integrate multiple modalities during surgery, including magnetic resonance imaging (MRI), positron emission tomography-computed tomography (PET-CT), endoscopy, ultrasound, fluoroscopy, and the ability to perform emergent endovascular procedures. 5-7 The patient is a 39-yr-old male, presenting after 19 yr follow-up of a surgical resection and proton beam treatment for a skull base chordoma. He developed progressive ophthalmoplegia due to recurrence of his chordoma at the right petrous apex and cavernous sinus. Preoperative angiography demonstrated narrowing of the petrous segment of the right carotid artery suspect of radiation-induced angiopathy. The presence of radiation-induced angiopathy increases the risk of intraoperative carotid rupture, and the availability of endovascular intervention in the operative suite added favorable preparedness to deal with such complications if they happen. Given the clinical and radiological progression, surgical intervention was carried out through the prior zygomatic approach with the goal of performing maximum resection. 8 The patient had an uneventful postoperative course and remained stable until he had a second recurrence 4 yr later. The patient consented to the procedure.